2016
DOI: 10.1264/jsme2.me16086
|View full text |Cite
|
Sign up to set email alerts
|

Missing Iron-Oxidizing Acidophiles Highly Sensitive to Organic Compounds

Abstract: The genus Acidithiobacillus includes iron-oxidizing lithoautotrophs that thrive in acidic mine environments. Acidithiobacillus ferrooxidans is a representative species and has been extensively studied for its application to the bioleaching of precious metals. In our attempts to cultivate the type strain of A. ferrooxidans (ATCC 23270T), repeated transfers to fresh inorganic media resulted in the emergence of cultures with improved growth traits. Strains were isolated from the resultant culture by forming colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…E6-1, 3-8 HM769771 (Figures 3 and 4, tailings and TIF) and Acidithiobacillus sp. NU-1_LC115032 ( Figures 3 and 4, bacterial enrichment) are phylogenetically similar to A. ferrooxidans ATCC19859 [38,39]. The detection of these acidophilic, iron-oxidizing bacteria is consistent with microbial communities from acid mine drainage environments [2,3,10,[17][18][19]21,[40][41][42][43].…”
Section: Interpreting Biogeochemical Processes Contributing To Tif Dementioning
confidence: 55%
“…E6-1, 3-8 HM769771 (Figures 3 and 4, tailings and TIF) and Acidithiobacillus sp. NU-1_LC115032 ( Figures 3 and 4, bacterial enrichment) are phylogenetically similar to A. ferrooxidans ATCC19859 [38,39]. The detection of these acidophilic, iron-oxidizing bacteria is consistent with microbial communities from acid mine drainage environments [2,3,10,[17][18][19]21,[40][41][42][43].…”
Section: Interpreting Biogeochemical Processes Contributing To Tif Dementioning
confidence: 55%
“…In another study, it was observed that the presence of lead, plastics, and other nonmetallic portions was found to be responsible for the reduced bacterial growth. 37 In a bioleaching process, the volume of inoculum is also considered to be a critical factor which directly influences the rate of bioleaching, as the number of active bacteria present in the medium increases with a rise in the volume of the inoculum. 31 Figure 8A depicts that there was an increase in the initial frequency of Cu extraction from CPCBs with an increase in the volume of inoculum from 5% to 25%.…”
Section: Resultsmentioning
confidence: 99%
“…The doubling time for each condition were compared (Ccorahua-Santo et al 2017) using the one-way ANOVA test followed by Tukey's test using GraphPad Prism version 6.0.0 for Windows (www.graphpad.com). The differences were considered to be significant at P < 0.05 (Ueoka et al 2016).…”
Section: Effect Of Temperature On Doubling Time In a Ferrooxidans Atc...mentioning
confidence: 99%